Stability indicating RP-HPLC method for estimation of cariprazine hydrochloride in human plasma - Shelke, Mohini; Godge, Rahul; Sahane, Tejas; Pawar, Onkar; Kasar, Sujata (Journal of Applied Pharmaceutical Research, 2024)
Objective: The objective of the study is to create and validate the easy, dependable, accurate, sensitive, and selective RP-HPLC method for estimating Cariprazine HCl in human plasma. Methodology: The sample was prepared using the protein precipitation extraction method. The chromatographic separation was performed with an AGILENT C18 column (250mm x 4.6ID) as the stationary phase and a mobile phase consisting of a 75:25 v/v solution of Methanol and 0.1% Orthophosphoric acid at a flow rate of 0.7 ml/min. The DAD detector was used to carry out the detection at 253 nm. Cariprazine HCl had a reduced retention duration of 2.46 minutes. Results & Discussion: The calibration curve had a correlation coefficient of 0.998 and was linear over the concentration range of 1–5µg/ml. The method's accuracy was shown at levels between 80%, 100%, and 120% of the specification limit. The developed method exhibited excellent precision, with interday precision ranging from 0.07% to 1.77% and intraday precision from 0.03% to 0.26%. It was discovered that the recovery of Cariprazine HCl was within the 98% range. Cariprazine HCl was discovered to have a Limit of Detection (LOD) of 0.053µg/ml, and the Limit of Quantification was found to be 0.160µg/ml. Conclusion: The solution was injected in duplicate, and the % RSD was measured. The results indicate that the proposed method can be effectively utilized for the routine analysis of Cariprazine HCl in human plasma. The forced degradation studies indicate that the drug is susceptible to Hydrolytic and Photolytic degradation